Strategi Pengembangan Petani Milenial Di Kabupaten Cilacap - Fathurahman, Fathurahman; Hariyadi, Hariyadi; Setianto, Novie Andri; Wulan, Tyas Retno; Sari, Lilik Kartika (Jurnal Pertanian Terpadu, 2025)
The quality of human resources is one of the factors that supports the success of agricultural development. One of the problems faced in agricultural development is the decreasing availability of human resources. The development of millennial farmers is an effort to sustain agriculture and attract the younger generation to play an active role in the agricultural sector. The study aims to describe the characteristics of millennial farmers and design a strategy for developing millennial farmers in Cilacap Regency. The analysis method used is qualitative descriptive analysis and SWOT analysis. The characteristics of millennial farmers in the use of technology are that technology is very supportive in agricultural activities. The competence of millennial farmers is a provision in farming. The work history before becoming a millennial farmer is a consideration for the millennial generation in making decisions to become millennial farmers. The results of the IFAS and EFAS analyses show that the internal factors of strength in the development of millennial farmers in Cilacap Regency include being responsive to technology and independent, while the weakness factors are low asset ownership, negative perception attitudes and laziness. Opportunity factors in EFAS in the development of millennial farmers in Cilacap Regency include advances in technology and information communication, government support and supporting officers and broad market opportunities. While the threat factors include climate change and pest and disease attacks, unsupportive regulations, fluctuating agricultural product prices and attractive job offers in the city. Strategies in developing millennial farmers include smart farming programs for millennial farmers, digital agricultural marketing training and capital grant assistance